The Structural Causes of Teacher Burnout in Hong Kong. Issue 6 (2nd November 2018) - Tsang, Kwok Kuen
Abstract: Since the mid 1990s, teacher burnout has become a crucial phenomenon in the Hong Kong education system, as increasing numbers of Hong Kong teachers have been reported as stressed, exhausted, and depersonalized in their teaching. In the Hong Kong community, including the academic circle, many people have applied the psychological theory of burnout to study the psychological causes of teacher burnout. However, this article argues that teacher burnout has become a social issue and is not a purely psychological phenomenon. Thus, it is important for us to identify the structural causes rather than the psychological causes of teacher burnout, to obtain a more comprehensive understanding of teacher burnout, and to develop better solutions. This article therefore theoretically analyzes how teacher burnout can be caused by certain structural forces, including structural education reforms, the administrative structure of schools, and the occupational and career structure of teaching, from the perspective of the sociological theory of work alienation. The article also gives recommendations for further studies based on the theoretical analysis.